PENERAPAN TECHNOLOGY ACCEPTANCE MODEL PADA MARKER BASED TRACKING UNTUK PEMBELAJARAN SISTEM TATA SURYA TERHADAP ANAK - ANAK - Awaludin, Muryan; Nugraha, Muhammad Rizki (Universitas Dirgantara Marsekal Suryadarma, 2021)
AbstractTechnology Acceptance Model (TAM) is a method used as a measurement tool in this study, to measure the feasibility of an Augmented Reality application by collecting questionnaire data on 150 respondents using 3 variables as a reference namely Perceived Easy Of Use as X1, Perceived Usefulness as X2, and Actual Use as Y. The data processing method uses SPSS 20 supporting applications with the data validation test process determination of the value of r table by finding df (degree of freedom) df = 150-2 with a significant 5% (0.1603) must < r count on each variable then the data is considered valid , the result of this data validation is 0.6210 which means the data is valid. And the reliability test with the provisions that the value at which the cronbach's alpha value must be > 0.6 for each variable, the data can be considered reliable, the results of the reliability test for the total of these three variables is 0.906 which means the data is reliable.Â Keywords: Augmented Reality, Technology Acceptance Model, Information and Communication Technology, Interactive Learning Media.